PENGARUH KEBIJAKAN DIVIDEN, INFLASI, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI (Studi Kasus Sektor consumer non-cyclicals yang Terdaftar Di BEI Tahun 2017 - 2021) - Sarah Qonita Lutfiah, (2022)
This quantitative research was conducted with the aim of knowing and analyzing the effect of dividend policy, inflation, and profitability on company value with corporate social responsibility as a moderating variable in consumer non cyclicals sector companies listed on the IDX in 2017-2021. The population and sample in this study are the non-cyclical consumer sector which is registerd on the IDX during 2017-2021. Data analysis in this study used Microsoft Excel 2016 and tested the hypothesis using panel data regression and moderation regression with the EViews 12 application. The results of this study indicate that, (1) dividend policy has no effect on firm value, (2) inflation has an effect positive to firm value, (3) profitability affects firm value, (4) corporate social responsibility does not moderate dividend policy on firm value, (5) corporate social responsibility moderates inflation on firm value, (6) corporate social responsibility moderates profitability to firm value company.